2009
DOI: 10.1103/physrevstper.5.010103
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the epistemological development of physics majors

Abstract: Students in introductory physics courses are likely to have views about physics that differ from those of experts. However, students who continue to study physics eventually become experts themselves. Presumably these students either possess or develop more expertlike views. To investigate this process, the views of introductory physics students majoring in physics are compared with the views of introductory physics students majoring in engineering. In addition, the views of physics majors are assessed at vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 13 publications
7
42
0
Order By: Relevance
“…Using these data, we demonstrated that, while pseudolongitudinal averages showed increases in students' E-CLASS scores in each consecutive course, analysis of longitudinal data indicates that this increase was not driven by a cumulative impact of laboratory instruction, but rather a selection effect in which students who persisted into higher level lab courses had started their lower level courses with more expertlike beliefs, attitudes, and expectations (as measured by E-CLASS) than their peers. This finding is consistent with prior work investigating longitudinal trends in a related assessment targeting students attitudes and beliefs in lecture physics courses, The Colorado Learning Attitudes about Science Survey [14,29].…”
Section: Discussionsupporting
confidence: 82%
“…Using these data, we demonstrated that, while pseudolongitudinal averages showed increases in students' E-CLASS scores in each consecutive course, analysis of longitudinal data indicates that this increase was not driven by a cumulative impact of laboratory instruction, but rather a selection effect in which students who persisted into higher level lab courses had started their lower level courses with more expertlike beliefs, attitudes, and expectations (as measured by E-CLASS) than their peers. This finding is consistent with prior work investigating longitudinal trends in a related assessment targeting students attitudes and beliefs in lecture physics courses, The Colorado Learning Attitudes about Science Survey [14,29].…”
Section: Discussionsupporting
confidence: 82%
“…Gire, Jones, and Price [529] used the CLASS survey to measure the epistemological development of physics majors. They administered the attitude survey to physics majors who were at different stages in their academic career, including students in their first, second, third, or fourth year of college, and graduate students in physics.…”
Section: Student Attitudes and Beliefs About Learning Physicsmentioning
confidence: 99%
“…III for details). Although a few previous studies [13][14][15][16] have reported epistemological variations among college students or postgraduates, none provided empirical explanations to account for such variations. In the current study, we first used the quantitative survey of CLASS to identify changes, if any, in the participants' views, and then followed with interviews to seek underlying mechanisms behind such changes.…”
Section: Introductionmentioning
confidence: 96%